2017
DOI: 10.1155/2017/8080649
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen-Month-Olds Adapt Their Imitative Behavior in Light of a Model’s Constraints

Abstract: Rather than reenacting every action they observe, preverbal infants adapt their imitative behavior. Although previous studies have revealed the capability of preverbal infants to imitate selectively, the question about the adaptability of this behavior on an individual level did not attract considerable scientific attention until now. In the current study, we investigated whether 14-month-old infants flexibly alternate their imitative response in accordance with a model's changing physical constraints in a bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…If infants are first familiarized with the blanket prior to the demonstration phases, differences between conditions disappear. When further manipulating the salience of the visual scene the authors were able to completely reverse the findings with respect to Gergely, Bekkering, and Király (2002; but see Gallén & Buttlemann, 2017 for a failure to replicate Beisert et al., 2012). This initial critique has since gained further support from studies demonstrating that visual attention can guide action selection in imitation studies; the visual makeup of the scene and attention grabbing‐ness of actions impact whether infants press the button with their head or hand (Daum, Vuori, Prinz, & Aschersleben, 2009; Keitel, Prinz, & Daum, 2014).…”
Section: Rational Imitationmentioning
confidence: 88%
“…If infants are first familiarized with the blanket prior to the demonstration phases, differences between conditions disappear. When further manipulating the salience of the visual scene the authors were able to completely reverse the findings with respect to Gergely, Bekkering, and Király (2002; but see Gallén & Buttlemann, 2017 for a failure to replicate Beisert et al., 2012). This initial critique has since gained further support from studies demonstrating that visual attention can guide action selection in imitation studies; the visual makeup of the scene and attention grabbing‐ness of actions impact whether infants press the button with their head or hand (Daum, Vuori, Prinz, & Aschersleben, 2009; Keitel, Prinz, & Daum, 2014).…”
Section: Rational Imitationmentioning
confidence: 88%
“… Gergely et al (2002) concluded that this is because infants evaluated actions according to their efficiency or rationality in the given situation ( Gergely and Csibra, 2003 ). This finding was replicated using similar paradigms and designs, and by testing even younger age groups ( Schwier et al, 2006 ; Buttelmann et al, 2008 ; Zmyj et al, 2009 ; Gellén and Buttelmann, 2017 ). In particular, Zmyj et al (2009) showed that 12- but not 9-month-old infants considered non-voluntary physical restraints (i.e., model’s hands tied to the table) when imitating unusual head-touch actions.…”
Section: Introductionmentioning
confidence: 74%
“…This study was designed to shed light on the neural mechanisms underlying infants’ observation of unusual head-touch actions used previously in selective imitation studies (e.g., Gergely et al, 2002 ; Gellén and Buttelmann, 2017 ). For this, we investigated the role of motor activation through measuring differences in mu frequency power.…”
Section: Discussionmentioning
confidence: 99%
“…Aunque este tipo de metodología se ha utilizado frecuentemente con niños entre 3 y 4,5 años (Gardiner, 2014;Kenward, 2012;Keupp, Bancken, Schillmöller, Rakoczy & Behne, 2016;Keupp, Behne & Rakoczy, 2013;Keupp, Behne, Zachow, Kasbohm & Rakoczy, 2015;Király, Csibra & Gergely 2013;Lyons, Young & Keil, 2007;McGuigan, Whiten, Flynn & Horner, 2007;Nielsen, Moore & Mohamedally, 2012;Taniguchi & Sanefuji, 2017), algunos autores introducen ciertas variaciones en las condiciones para investigar el desarrollo de la comprensión intencional en edades más tempranas -entre los 12 y 14 meses- (Gellén & Buttelmann, 2017;Zmyj, Daum & Aschersleben, 2009). Los cambios realizados repercuten, a su vez, en la interpretación de las acciones del niño.…”
Section: Metodologías Activasunclassified